Human microbial metabolite mimicry as a strategy to expand the chemical space of potential drugs - Li, Hao; Ranhotra, Harmit S; Mani, Sridhar; Dvořák, Zdeněk; Sokol, Harry; Müller, Rolf (Drug discovery today, 2020)
The concept of small-molecule mimicry even of weak microbial metabolites present in rodents and humans, as a means to expand drug repertoires, is new. Hitherto, there are few proof-of-concept papers demonstrating utility of this concept. More recently, papers demonstrating mimicry of intestinal microbial metabolites could expand the drug repertoire for diseases such as inflammatory bowel disease (IBD). We opine that, as more functional metabolite-receptor pairings are discovered, small-molecule metabolite mimicry could be a significant effort in drug discovery.
Keywords: mikrobiota; Drug Discovery; Molecular Mimicry; Animals; lidé; objevování léků; molekulární mimikry; Microbiota; Humans; zvířata